Advances in immunology. Volume 16 - Dixon, Frank J. (Frank James), 1920-2008.; Kunkel, Henry G., 1916-1983.; ScienceDirect eBooks (New York ; London : Academic Press, 1973)
ADVANCES IN IMMUNOLOGY VOLUME 16.
V. Spontaneous Immune Complex Disease of Unknown Cause in AnimalsVI. Glomerulonephritis of Possible Immune Complex Origin in Humans; VII. Vasculitis of Possible Immune Complex Origin in Humans; VIII. Methods of Detecting Immune Complexes in Serum; References; Chapter 5. The Immunopathology of Joint Inflammation in Rheumatoid Arthritis; I. Introduction; II. Normal Synovial Membrane; III. Rheumatoid Arthritis; IV. Role of Rheumatoid Factors in Rheumatoid Joint Inflammation; V. Conclusions; References; Notes Added in Proof; Author Index; Subject Index.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Immunology; MEDICAL -- Immunology; Immunité.; Immunology; Electronic books